(untitled) - Tompkins, James A. (Norcross, 1989)
This practical book provides a blueprint for the dramatic improvement of any company's manufacturing operation on an ongoing basis. It presents and details twenty "Requirements of Success" for pursuing successful manufacturing including: costs, product development, marketing, lead times, material flow, inventories, maintenance, quality, and human resources. This book was originally published in 1989 by the Institute of Industrial Engineers in the USA and was sold by the Institute primarily to its membership.
Keywords: Production management,Quản lý sản xuất